Violence, Burnout and Minor Psychiatric Disorders in Hospital Work - Daiane Dal Pai; Liana Lautert; Sônia Beatriz Cocaro de Souza; Maria Helena Palucci Marziale; Juliana Petri Tavares
OBJECTIVE Identifying the violence suffered by the health team workers and their association with Burnout and minor psychiatric disorders. METHODS Cross-sectional study with 269 health team professionals of a public hospital in southern Brazil. Data were collected through the use of the Survey Questionnaire: Workplace Violence in the Health Sector, Maslach Inventory Burnout and Self-Report Questionnaire. RESULTS Workplace violence struck 63.2% of workers, prevailing mostly in women (p = 0.001), among nursing auxiliaries/technicians (p=0.014) and was associated with minor psychiatric disorders (p<0.05), as exposure to different forms of violence increased the chances of these disorders by 60% (CI 95%: 1.2-2.1). The three Burnout dimensions were also associated to violence at work (p<0.05). CONCLUSION Health workers experience violence in the workplace and this exposure is associated with Burnout symptoms and minor psychiatric disorders.